Age-Related Scanning Electron Microscopic Studies on the Articular Cartilage of Femoral Head in Buffaloes (Bubalus bubalis) - Ranjith Kumar S,; Pramod Kumar D,; Purusthotham G,; Lakshman M,; Chandra sekhara EL, (Indian Journal of Veterinary Anatomy, 2026)
Femoral head articular cartilages of 24 apparently healthy buffaloes irrespective of their breed, sex and nutritional status were procured from local slaughter houses in and around Hyderabad. Collected specimenswere divided into four groups viz., Group I (Prenatal stage)and three post-natal stages such as Group II (neonatal), Group III (young adult) and Group IV (aged). Scanning electron microscopic features of articular surface of femoral head articular cartilage in Group-I revealed a continuous surface without any break with longitudinal folds and numerous tightly packed chondrocytes, which were unidirectional and protruding outwards, separated by fine grooves. At much higher magnification, uniformly dispersed chondrocytes protruded as hemispherical, irregular or spindle-shaped elongations. In Group-II and III specimens articular cartilage surface of femoral head was smoother with few erythrocytes. Protrusions of chondrocytes were seen along with numerous minute debris of synovial fluid secretions. At the junction of articular cartilage and sub-chondral bone, cartilage matrix was smoother and osseous part comprised collagen fibres. Femoral head articular cartilage surface in specimens of Group III and IV revealed an uneven outline with deeply located cells and remnants of synovial fluid. Few cells were surrounded by a furrow caused by collapse of pericellular matrix. These findings demonstrate a progressive transition from a highly organized and proliferative chondrocytic arrangement in prenatal cartilage to smoother, functionally adapted surfaces in postnatal stages, followed by structural deterioration in aged animals. This study confirmed that the femoral head articular cartilage of buffaloes undergoes progressive degeneration as the age advances.